Clinical characteristics and predictors for hospitalisation during the initial phases of the Delta variant COVID‐19 outbreak in Sydney, Australia. (1st August 2022) - Davis, Rebecca; Bein, Kendall; Burrows, Jamie; Chakar, Bashir; Berendsen Russell, Saartje; Hutchings, Owen; Dearing, Cassandra; Jagers, Dianna; Edwards, James; Chalkley, Dane; Shaw, Miranda; McKenzie, Lucy; et al.
Abstract: Objectives: The COVID‐19 Delta variant of concern continues to pose significant challenges to health systems globally, with increased transmissibility and different patient populations affected. In Sydney, a virtual model of care was implemented in response to the COVID‐19 pandemic and Special Health Accommodation (SHA) was made available for community patients with COVID‐19 who could not isolate at home or needed health support. Methods: This retrospective observational cohort study of all patients with COVID‐19 Delta variant in SHA during the initial phases of the Delta variant outbreak in Sydney describes the demographic and clinical characteristics of patients with Delta variant COVID‐19 and determines predictors of need for in‐patient hospital admission. Results: Data from 794 patients were analysed. One hundred and fifty‐seven patients (19.8%) were transferred to ED. Of those, 125 were admitted to an in‐patient unit (admission rate from ED 79.6%), and of these 30 (24%) went to ICU and seven were intubated. Two patients died within the follow‐up period. Age >40 years, obesity, and presence of fever (temperature >37.5°C), hypoxia (oxygen saturation <95%), tachycardia or gastrointestinal symptoms on initial assessment in SHA were independent predictors of in‐patient admission with an AUROC of 0.78 (95% confidence interval 0.73, 0.82). Conclusions: Initial symptoms and vital signs were just as predictive for short‐term deterioration as age and pre‐existing comorbidities and should be included in future risk prediction models for COVID‐19. Based on this, we derive a proposed risk prediction score that incorporates these predictors with further validation required.